Implementing and Operating Computer Graphics in the Contemporary Chemistry Education - Popovska, Olga (Mediterranean journal of chemistry, 2017)
Technology plays a crucial role in modern teaching, providing both, educators and students fundamental theoretical insights as well as supporting the interpretation of experimental data. In the long term it gives students a clear stake in their learning processes. Advancing in education furthermore largely depends on providing valuable experiences and tools throughout digital and computer literacy. Here and after, the computer’s benefit makes no exception in the chemistry as a science. The major part of computer revolutionizing in the chemistry laboratory is with the use of images, diagrams, molecular models, graphs and specialized chemistry programs. In the sense of this, the teacher provides more interactive classes and numerous dynamic teaching methods along with advanced technology. All things considered, the aim of this article is to implement interactive teaching methods of chemistry subjects using chemistry computer graphics. A group of students (n = 30) at the age of 18–20 were testing using methods such as brainstorming, demonstration, working in pairs, and writing laboratory notebooks. The results showed that demonstration is the most acceptable interactive method (95%). This article is expected to be of high value to teachers and researchers of chemistry, implementing interactive methods, and operating computer graphics